The Effectiveness of the Combination of Lethal Ovitrap Attractant of Local Organic Materials and Natural Larvicides in Dengue Hemorrhagic Fever Endemic Areas - Erlin Yustin Tatontos; I Wayan Getas; Urip Urip (Postgraduate, University of Mataram, 2022)
Dengue fever is a viral infection that is transmitted to humans through the bite of an infected mosquito. Dengue prevention and control depends on effective vector control measures, including lethalovitrap.The purpose of this study was to determine the effectiveness of mango leaf infusions (Mangifera indica), rambutan leaves (Nephelium lappaceum) and cashew leaf (Anacardium ocidentale) in lethal ovitrap a combination of ethanol extract of rambutan leaves (Nephelium lappaceum), srikaya seed water extract (Annona squomosa) and Baccilus thuringiensis var israelensis (Bti) in the endemic area of â€‹â€‹Mataram City Dengue Fever, This study was an experimental study that tested and analyzed the effectiveness ofÂ nine lethal ovitrap atractant combination. The population and sample of this study were Aedes aegypti mosquitoes female from colonization from endemic areas of DHF in Mataram City. The laboratory test results from nine effective lethal ovitrap combination attractants were Cashew leaf infusion and Rambutan leaf ethanol extract with trapped eggs of Aedes aegypti mosquitoes averaging 133 grains and no eggs hatching into larvae. Statistical analysis with ANOVA followed by the Tukey HSD post-Hoc test with a significant difference of <0.05 the effectiveness of the combination of lethal ovitrap attractants, especially Cashew leaf infusion and ethanol extract from rambutan leaves and Rambutan leaf infusion and rambutan leaf ethanol extract. The results of the field test were the percentage of the number of eggs trapped in combination of Cashew leaf infusion (41.6%) and Rambutan leaf infusion with ethanol extract of Rambutan leaves (58.4%).